The Reliability and Validity of the Malay Version of Polycystic Ovarian Syndrome Health-Related Quality of Life Questionnaire - Mei, Lim Leek; Abu, Muhammad Azrai; Chew, Kah Teik; Ismail, Aniza; Zainuddin, Ani Amelia; Nur Azurah, Abdul Ghani (Frontiers in Endocrinology, 2022)
The polycystic ovary syndrome questionnaire is a reliable instrument for measuring health-related quality of life. This study aimed to develop a Malay version of the polycystic ovary syndrome questionnaire and to evaluate the health-related impact of Malaysian women with polycystic ovary syndrome. Participants were women who were diagnosed with polycystic ovary syndrome using Rotterdam criteria in the gynaecology clinic. Reliability was determined by internal consistency using Cronbach’s coefficient alpha and test-retest reliability using intra-class correlation coefficient. Validity was assessed through convergent and discriminant validity. Examining the correlation between similar content of the Malay version of polycystic ovary syndrome questionnaire and the SF-36 assessed convergent validity. The discriminant validity was assessed using the known group comparison. Cronbach’s alpha coefficient was over 0.70 for total scale and over 0.60 for each subscale. Known group comparison supported the discriminant validity. The Malay version of polycystic ovary syndrome questionnaire differentiated the sub-groups of women who differed in polycystic ovary syndrome-specific symptoms. Convergent validity was consistent with the good positive correlation between related subscales of the two instruments. Polycystic ovary syndrome women in Malaysia scored the lowest for weight (3.74) and infertility (3.41) domains, thereby indicating worse health status in these domains. Body hair (5.42) was the least troublesome for the local population. The Malay version of polycystic ovary syndrome questionnaire is a reliable and valid tool for assessing the health-related quality of life among the women in the local population. It can be used to objectively assess the quality of life among Malaysian women with polycystic ovary syndrome and evaluate their responsiveness to treatment modalities.